2010
DOI: 10.1002/pssc.200982472
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and biomolecular interfaces to metal oxide semiconductors

Abstract: Previous work has shown that organic alkenes will graft to covalent semiconductors such as diamond and silicon. Here, we demonstrate that organic alkenes can be grafted to the surfaces of metal oxide semiconductors, including TiO2 in nanocrystalline thin films and as single‐crystal anatase(001) epitaxial films grown on SrTiO3(001) substrates. The resulting layers can be used as a starting point for linking biomolecules such as DNA to metal oxide surfaces. Initial results are presented showing that this chemist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 30 publications
(62 reference statements)
0
14
0
2
Order By: Relevance
“…Analysis of the high-resolution spectra of Ti 2p (Figure 1b) indicates that Ti element on the surface was mainly in Ti 4+ –O form, showing two major spin–orbit components unique to TiO 2 at about 458.2 and 464.2 eV, respectively. 2224 In Figure 1, the main contribution of O 1s (binding energy 530.1 eV) originates from the oxygen in the TiO 2 substrate. 34 The shoulder peak near 531.5 eV is similar to those reported previously from physisorbed water, oxidized carbon species, and partially hydroxylated TiO 2 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Analysis of the high-resolution spectra of Ti 2p (Figure 1b) indicates that Ti element on the surface was mainly in Ti 4+ –O form, showing two major spin–orbit components unique to TiO 2 at about 458.2 and 464.2 eV, respectively. 2224 In Figure 1, the main contribution of O 1s (binding energy 530.1 eV) originates from the oxygen in the TiO 2 substrate. 34 The shoulder peak near 531.5 eV is similar to those reported previously from physisorbed water, oxidized carbon species, and partially hydroxylated TiO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…2224 A set of control experiments was performed to test whether it was necessary to protect the alkyne by TMG group during the photochemical grafting (see Supporting Information, Figure S1). The results showed that if the vinyl group in TMG-C10 was replaced by an ethynyl group, the molecule could also attach on the TiO 2 substrate under identical irradiation conditions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Analoge photochemische Reaktionen wurden auf ZnO(1010)‐Einkristallen und ZnO‐Nanostäbchen,141 Zirconiumoxid,142 dünnen Filmen aus SnO 2 ‐Nanopartikeln143 und GaN beobachtet 144. Im letztgenannten Fall binden die Moleküle, wie in Abbildung 40 gezeigt, über eine Ga‐O‐C‐Brücke an die GaN‐Oberfläche.…”
Section: Alkene Und Alkineunclassified